ART THERAPY AS A STRATEGY TO PROMOTE POLICE OFFICER’S QUALITY OF LIFE IN WORK STRESS - Linduina Mendes Maia, Maria (Health and Society, 2022)
Objective: to list aspects of art therapy as an ally in the process of prevention, health promotion and improvement of the policeman’s quality of life in reducing the level of work stress. Methodology: This is a literature review, carried out from January 2022 to July 2022, from the Virtual Health Library (VHL) in the databases, LILACS and in the SCIELO electronic library Revistas Eletrônicas, Theses, dissertations and other bases, having as descriptors “art therapy, police, stress and quality of life. Results: the articles and literature demonstrated the therapeutic potential that art therapy has and it is perceived as an important strategy contributing in a relevant and profound way to the human being in the world, being a welcoming and healing resource for people with stress and in the most different. contexts, linked to the commitment that the subject reconstituted himself as the author of his own history.